2023
DOI: 10.3390/mi14112112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Block Copolymer Terminal Groups on Toughening Epoxy-Based Composites: Microstructures and Toughening Mechanisms

Gang Li,
Wenjie Wu,
Xuecheng Yu
et al.

Abstract: Despite the considerable research attention paid to block copolymer (BCP)-toughened epoxy resins, the effects of their terminal groups on their phase structure are not thoroughly understood. This study fills this gap by closely examining the effects of amino and carboxyl groups on the fracture toughness of epoxy resins at different temperatures. Through the combination of scanning electron microscopy and digital image correlation (DIC), it was found that the amino-terminated BCP was capable of forming a stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Its optimal delamination resistance index was 74, demonstrating excellent delamination resistance ( Table 6 ). Amino end-capped PCBs prepared by Li et al [ 113 ] as a second-phase modifier increased the fracture toughness of EP/Amino-BCP/SiO 2 at room temperature by 31.2% in the presence of 60 wt% SiO 2 ; CTE1 increased by 6.1 ppm/K; and CTE2 was largely unaffected. Through comparative experiments, Yang et al [ 114 ] found that amino block copolymers and silicone block copolymers showed a good toughening mechanism as toughening agents for bottom filling.…”
Section: The Most Recent Solutions For Delamination Failurementioning
confidence: 99%
“…Its optimal delamination resistance index was 74, demonstrating excellent delamination resistance ( Table 6 ). Amino end-capped PCBs prepared by Li et al [ 113 ] as a second-phase modifier increased the fracture toughness of EP/Amino-BCP/SiO 2 at room temperature by 31.2% in the presence of 60 wt% SiO 2 ; CTE1 increased by 6.1 ppm/K; and CTE2 was largely unaffected. Through comparative experiments, Yang et al [ 114 ] found that amino block copolymers and silicone block copolymers showed a good toughening mechanism as toughening agents for bottom filling.…”
Section: The Most Recent Solutions For Delamination Failurementioning
confidence: 99%
“…Additionally, the performance of core-shell particles can be regulated by altering the types of monomers [14,15] . However, due to weak interfacial interactions and poor dispersibility [16,17] , simply blending core-shell modi ers with the matrix polymer often fails to achieve satisfactory toughening effects [18][19][20][21] . Reactive compatibilization is an effective method to enhance the interfacial strength and compatibility between the toughening agent and the matrix [22] .…”
Section: Introductionmentioning
confidence: 99%